Winter and summer sedimentary dynamic process observations in the sea area off Qinhuangdao in the Bohai Sea, China - Deqiang Zhang; Deqiang Zhang; Chongguang Pang; Chongguang Pang; Chongguang Pang; Zhiliang Liu; Zhiliang Liu; Jingbo Jiang; Jingbo Jiang; Jingbo Jiang (Frontiers in Earth Science, 2023)
Sedimentary processes in marginal seas play an important role in the biology, physics, and geochemistry as well as ecology of coastal environments and contain abundant information about the material transfer from land to ocean and the regional circulation. Due to the huge sediment discharge of the Yellow River, the Bohai Sea, China is one of the areas with the highest suspended sediment concentration (SSC) in the world. Interestingly, the SSC at the west of the Bohai Sea is low all year round. Thus, it is of great significance to examine the sedimentary dynamic process in this area for better understanding the circulation structure, material exchange and regional environment of the Bohai Sea. Using seabed base observation platform measurements obtained in February 2017 and August 2019, this study examines the winter and summer hydrography and suspended sediment concentration in the sea area off Qinhuangdao located to the west of the Bohai Sea. In summer, the relatively weak residual currents flowed northeastward and showed little correlation with the wind field, especially in the middle layer of the water column. In winter, the residual currents were strengthened, flowing to the northeast during strong wind periods, and predominantly to the southwest during intermittent periods. Moreover, driven by the pressure gradient force associated with the wind-induced sea surface height variations, the winter current was closely related to the wind speed, with correlation coefficients ranging from 0.4 to 0.6 and a time lag of 10 h. The summer SSC was lower and mainly controlled by the tidal current, whereas in winter, owing to the enhanced Reynolds stress and turbulent kinetic energy, strong wind bursts triggered significant sediment resuspension and led to a higher SSC. For the suspended sediment flux (SSF), the advection terms contributed more than 80% in the winter and summer, while the vertical circulation terms contributed 13% in winter, and approximately half that much in summer. Generally, the suspended sediment is transported back and forth, with a little net northward and northeastward motions in winter and summer, respectively. This may explain the low SSC sustaining in coastal Qinhuangdao all year round. These results provide a reference for sedimentary studies conducted in other coastal waters, especially in monsoon-dominating shelf seas.